我國高齡教育基本權的憲法基礎探究：終身學習權保障觀點 Study of the Constitutional Foundations of the Right to Senior Education in Taiwan: A Lifelong-Learning-Right Perspective - 王等元 Deng-Yuan Wang (National Taiwan Normal University, 2018)
個別基本權利功能及其憲法保障基礎的探究是基本權利理論研究的重要問題；故本研究從終身學習權保障觀點出發，並以教育憲法釋義學方法，試圖探究我國新興高齡教育基本權功能及其憲法保障基礎。本研究發現，為因應臺灣高齡社會發展趨勢，高齡教育基本權利應屬國民教育基本權與大學學術自由以外的新興教育基本權利，其憲法保障的基礎為我國立國精神之憲法基本原則、憲法第 22 條「概括基本權利」，以及基本國策相關規定；其次，我國高齡教育基本權應具有防禦權功能、客觀價值秩序功能、制度性保障功能，以及組織與程序功能；最後，就其基本權功能而言，除防禦權功能外，其餘應屬基本權客觀法規範功能，旨在課予國家積極提供高齡學習機會之作為義務，以協助人民實現其高齡教育基本權利。 Discussions of individual basic rights and their constitutional protection are fundamental to research into basic rights theory. This paper aims at explicating the functions of the basic right to senior education and its constitutional rationale through interpretative epistemology of the Constitution from a lifelong-learning-right perspective. The research findings are as follows: (1) In global aging societies, the basic right to senior education is a relatively new right to education, and its constitutional rationale can be derived from articles 11 and 22 of the Constitution. (2) The functions of the basic right to senior education are the defensive function, objective values function, institutional protection function, and organizational and procedural function. (3) Except for the first function, the others are new basic-right functions, which impose the state obligations to help the older adults benefit from the right to senior education. On the basis of these findings, some suggestions for policy decision-makers and future research are provided.